Comparative Analysis Of Financial Performance Before And After Acquisition: Case Study On PT Plaza Indonesia Realty, TBK (2012-2018) - Nafisa, Kafka; Susena , Karona Cahya (Universitas Dehasen Bengkulu, 2025)
This study aims to analyze the impact of acquisition on the performance of financial companies at PT Plaza Indonesia reality,Tbk.the company’s finansial performance is measured usung finansial ratios,including: liquidity rasio, activity rasio, profitability ratio,market value rasio and solvency rasio. Where acquisition is a merger of two companies where the acquisitor company busy some of the shares of the acquired company, si that management control of the acquired company is transferred to the acquisitor company. This study uses secondary data. While the population of this study includes the annual finansial report of PT Plaza Indonesia reality Tbk which is listed on the Indonesia stock exchange(IDX).